Monopoli Pada Industri Perkebunan Kelapa Sawit: Kajian Hukum Atas Perubahan Peraturan Kementerian Pertanian No.98/2013 - Setiawan, Rania Nur Hafsah; Nur Hafsah Setiawan, Rania (UNES Law Review, 2024)
This research reviews the impact of the removal of articles in the Minister of Agriculture Regulation No. 98/2013 on the regulation and dynamics of business competition in the palm oil plantation industry, as well as monopolistic practices. The removal of several articles potentially damages business relationships and leads to unhealthy business competition. This research aims to provide an understanding of the impact of regulatory changes on the palm oil plantation industry. Using a qualitative approach, it focuses on analyzing the potential monopolistic practices occurring in the palm oil industry as a direct result of the removal of Articles 13, 14, and 49. By analyzing secondary data and related literature, this research identifies new patterns in business competition dynamics and how these changes affect various stakeholders. The results of the study are expected to provide insights into the changes resulting from the removal of these articles. Recommendations provided include strengthening regulations and exploring alternatives to maintain healthy business competition.